Visual performance, light distortion and patient reported outcomes with a new bi-aspheric non-diffractive extended depth of focus intraocular lens - Tañá-Sanz, Santiago; Tañá-Sanz, Pedro; Elvira-Giner, Belén; Orts-Vila, Paz; Tañá-Rivero, Pedro (Frontiers in Medicine, 2025)
BackgroundTo evaluate refractive, visual, and patient-reported outcomes three months after bilateral implantation of a novel bi-aspheric, non-diffractive extended depth of focus (EDOF) intraocular lens (IOL) using PhaseRing technology to achieve good vision across distances with reduced dysphotopsia.MethodsTwenty-two patients received bilateral Asqelio EDOF IOLs (AST VisionCare Inc.) and were evaluated 3 months post-surgery. The main outcomes assessed were refractive error, monocular and binocular visual acuities at distance, intermediate (67 cm) and near (40 cm), low contrast visual acuity, defocus curves, contrast sensitivity, and patient questionnaires.ResultsThe average postoperative spherical equivalent was −0.31 ± 0.30 D. Astigmatism of ≤ 1.00 D was present in all eyes (100%, n = 44), with 75% (n = 33) showing astigmatism of ≤ 0.50 D. Every patient attained a corrected distance visual acuity (CDVA) of 20/25 or better and a distance-corrected intermediate visual acuity (DCIVA) of 20/32 or better. Contrast sensitivity met or exceeded normal levels under both photopic and mesopic conditions, with and without glare, except at 12 cycles per degree under mesopic conditions with glare. Light distortion index was comparable to published reports on monofocal IOLs and other non-diffractive EDOF IOLs, and lower than diffractive multifocal IOLs. Post-surgery, 90.9% (n = 20) of patients reported being satisfied with their vision. No significant visual symptoms were reported.ConclusionAsqelio™ EDOF IOL offers an efficient design, providing good clinical outcomes for distance and intermediate vision, while some patients reach functional levels of near vision. Its non-diffractive design minimizes dysphotopsia and reduces light distortion compared to other presbyopia-correcting IOLs.